ENHANCING STUDENTS’ PHYSICAL ABILITIES THROUGH GYMNASTICS DISCIPLINES: AN EVIDENCE-INFORMED SCHOOL-BASED FRAMEWORK - Shaydullayeva Guliruxsor Jumanazarovna (Prospects for innovative technologies in science and education, 2025)
Schools are a key setting for developing students’ physical abilities (strength, flexibility, balance, coordination, speed, and endurance). Gymnastics—across multiple disciplines—offers structured, scalable movement experiences that can strengthen health-related fitness and movement competence. World Gymnastics recognizes eight disciplines (e.g., artistic, rhythmic, trampoline & tumbling, acrobatics, aerobics, parkour), many of which can be adapted for physical education (PE).